Review Literatur: Pengaruh Pendidikan Kesehatan Terhadap Pemahaman Masyarakat Tentang HIV/AIDS - Nina Salsabilla; Reyna Agesti (Awatara Publisher, 2026)
HIV and AIDS remain major global public health challenges, particularly among adolescents who are vulnerable to risky behaviors due to psychosocial factors and limited access to accurate information. Health education is considered a strategic intervention to improve knowledge, reduce stigma, and promote preventive behaviors related to HIV/AIDS. This study aims to analyze the effectiveness of health education in improving public understanding and attitudes toward HIV/AIDS and to identify factors influencing its transmission and prevention. This study employed a systematic literature review approach by analyzing scientific articles obtained from electronic databases including Google Scholar, ProQuest, and Semantic Scholar. Relevant articles related to HIV/AIDS knowledge, attitudes, stigma, risk factors, and health education interventions were selected and reviewed using a descriptive synthesis approach. The findings show that health education consistently contributes to increased knowledge and the development of positive attitudes toward HIV/AIDS. Adequate knowledge is associated with reduced stigma and improved preventive practices. Individual characteristics such as age, education level, gender, and access to information significantly influence knowledge levels. In addition, geographical factors contribute to variations in transmission patterns and case distribution. Health education plays a crucial role in HIV/AIDS prevention. Effective interventions should be designed based on demographic and geographical characteristics of the target population and incorporate participatory and stigma-reduction approaches to achieve sustainable behavioral change.